2020
DOI: 10.1007/s13721-020-00263-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking suggests repurposing of brincidofovir as a potential drug targeting SARS-CoV-2 ACE2 receptor and main protease

Abstract: The current outbreak of the highly transmittable and life-threatening severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has evolved rapidly and posed a global health emergency. Many clinical trials are now being conducted to test possible therapies. To assist this, virtual screening via molecular docking was performed on several FDA-approved drugs, previously used in epidemics, and the top ten compounds were selected. These ten well-characterized drugs, previously used to treat malaria and Ebola inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The solubility of small molecules impacts their bioavailability and the need for frequent dosing, hence we investigated the ADME properties, inhibition of cytochrome P450 (CYP), modulation of P-glycoprotein (Pgp), solubility, plasma protein binding and permeability of the top scoring compounds in our analysis. The best scoring compounds for both SARS-CoV-2 M pro and spike glycoprotein were tested for obeying Lipinski’s rule of five parameters, which states that drugs having log P ranging from 0 to 5, have high possibility of oral absorption [ 42 ]. Data ( Table 2 ) showed that the compounds have log P values that ranged from −1.06 to 2.8 that does not exceed 5.0 indicating reasonable probability of their good absorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solubility of small molecules impacts their bioavailability and the need for frequent dosing, hence we investigated the ADME properties, inhibition of cytochrome P450 (CYP), modulation of P-glycoprotein (Pgp), solubility, plasma protein binding and permeability of the top scoring compounds in our analysis. The best scoring compounds for both SARS-CoV-2 M pro and spike glycoprotein were tested for obeying Lipinski’s rule of five parameters, which states that drugs having log P ranging from 0 to 5, have high possibility of oral absorption [ 42 ]. Data ( Table 2 ) showed that the compounds have log P values that ranged from −1.06 to 2.8 that does not exceed 5.0 indicating reasonable probability of their good absorption.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, two SARS-CoV-2 proteins which facilitate viral–host interaction and replication were selected from the RCSB protein databank ( , accessed on 20 February 2021). The proteins are SARS-CoV-2 main protease (PDB ID: 6LU7, resolution = 2.16 Å) [ 54 ] and spike glycoprotein (PDB ID: 6M0J, resolution = 2.45 Å) [ 42 ]. The 3D protein structures were prepared using Molecular Operating Environment software (MOE 2014.0901) Ligx option.…”
Section: Methodsmentioning
confidence: 99%
“…A virtual screening method identified cidofovir as a potentially effective therapeutic against SARS-CoV-2 [ 48 ]. A molecular docking study suggests the repurposing of brincidofovir against SARS-CoV-2 [ 49 ]. For favipiravir, several clinical trials are listed in the ClinicalTrials database hosted by the U.S. National Library of Medicine [ 50 ], running in several countries, including Italy (NCT04336904), Turkey (NCT04474457), and the United States (NCT04358549).…”
Section: Discussionmentioning
confidence: 99%
“…A virtual screening method identified cidofovir as a potentially effective therapeutic against SARS-CoV-2 [48]. A molecular docking study suggests the repurposing of brincidofovir against SARS-CoV-2 [49]. For favipiravir, several clinical trials are listed in the Clinical-Trials database hosted by the U.S. National Library of Medicine [50], running in several countries, including Italy (NCT04336904), Turkey (NCT04474457), and the United States (NCT04358549).…”
Section: Discussionmentioning
confidence: 99%